First Generation of Antioxidant Precursors for Bioisosteric Se-NSAIDs: Design, Synthesis, and In Vitro and In Vivo Anticancer Evaluation - Sandra Ramos-Inza; Cesar Aliaga; Ignacio Encío; Asif Raza; Arun K. Sharma; Carlos Aydillo; Nuria Martínez-Sáez; Carmen Sanmartín; Daniel Plano (MDPI AG, 2023)
The introduction of selenium (Se) into organic scaffolds has been demonstrated to be a promising framework in the field of medicinal chemistry. A novel design of nonsteroidal anti-inflammatory drug (NSAID) derivatives based on a bioisosteric replacement via the incorporation of Se as diacyl diselenide is reported. The antioxidant activity was assessed using the DPPH radical scavenging assay. The new Se-NSAID derivatives bearing this unique combination showed antioxidant activity in a time- and dose-dependent manner, and also displayed different antiproliferative profiles in a panel of eight cancer cell lines as determined by the MTT assay. Ibuprofen derivative 5 was not only the most antioxidant agent, but also selectively induced toxicity in all the cancer cell lines tested (IC50 < 10 µM) while sparing nonmalignant cells, and induced apoptosis partially without enhancing the caspase 3/7 activity. Furthermore, NSAID derivative 5 significantly suppressed tumor growth in a subcutaneous colon cancer xenograft mouse model (10 mg/kg, TGI = 72%, and T/C = 38%) without exhibiting any apparent toxicity. To our knowledge, this work constitutes the first report on in vitro and in vivo anticancer activity of an unprecedented Se-NSAID hybrid derivative and its rational use for developing precursors for bioisosteric selenocompounds with appealing therapeutic applications.